2020
DOI: 10.3847/2041-8213/ab8c44
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Iron Emission Lines from the Dayside of KELT-9b: The GAPS Program with HARPS-N at TNG XX

Abstract: We present the first detection of atomic emission lines from the atmosphere of an exoplanet. We detect neutral iron lines from the dayside of KELT-9b (T eq ∼4000 K). We combined thousands of spectrally resolved lines observed during one night with the HARPS-N spectrograph (R∼115,000), mounted at the Telescopio Nazionale Galileo. We introduce a novel statistical approach to extract the planetary parameters from the binary mask crosscorrelation analysis. We also adapt the concept of contribution function to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
53
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(66 citation statements)
references
References 76 publications
10
53
2
Order By: Relevance
“…For Fe, we find that Fe/H = 1.2 × 10 −8 , which is much lower than solar ratios. This ratio implies that the species must also be found in another form, which matches the findings in Pino et al (2020) who detected atomic Fe, even though their assumed self-consistent temperature structure from Lothringer et al (2018) differs from our retrieved ones.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…For Fe, we find that Fe/H = 1.2 × 10 −8 , which is much lower than solar ratios. This ratio implies that the species must also be found in another form, which matches the findings in Pino et al (2020) who detected atomic Fe, even though their assumed self-consistent temperature structure from Lothringer et al (2018) differs from our retrieved ones.…”
Section: Discussionsupporting
confidence: 87%
“…Given the extreme temperatures, the majority of molecules are anticipated to be dissociated leaving only atomic species (Kitzmann et al 2018). Ground-based high-resolution observations have detected a number of metals including iron, titanium, and calcium (Hoeijmakers et al 2018(Hoeijmakers et al , 2019Cauley et al 2019;Yan et al 2019;Pino et al 2020;Turner et al 2020). Observations of KELT-9 b with TESS and Spitzer have revealed an asymmetric transit (Ahlers et al 2020), induced by the fast rotation of its host star.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This corresponds to probing about an order of magnitude in pressure between 10 and 100mbar, useful for determining the presence and magnitude of temperature inversions which are predicted to be ubiquitous in the hottest Jovian planets (Lothringer et al 2018). Indeed, a temperature inversion has recently been detected in KELT-9b from ground-based high-resolution observations of neutral Fe (Pino et al 2020).…”
Section: Kelt-9bmentioning
confidence: 99%
“…The signature of Fe i has since been detected in the transmission spectrum of several hot Jupiters, including KELT-9b (Hoeijmakers et al 2018), WASP-121b (Gibson et al 2020;Cabot et al 2020;Bourrier et al 2020), WASP-76b (Ehrenreich et al 2020), and KELT-20b/MASCARA-2b (Nugroho et al 2020;Stangret et al 2020;Hoeijmakers et al 2020). Recently, Pino et al (2020) detected Fe i in the dayside spectrum of KELT-9b for the first time using the data taken with HARPS-N on the Telescopio Nazionale arXiv:2007.05508v1 [astro-ph.EP] 10 Jul 2020 Galileo. They also showed that the Fe i signature is in emission, which provides direct evidence of a thermal inversion.…”
Section: Introductionmentioning
confidence: 99%